Rasionalitas Penggunaan Obat Antihipertensi di Puskesmas Pinang Jaya Kota Bandar Lampung - Pratama, Rendiko Agung Candra; Ulfa, Ade Maria; Rudy, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
Hypertension is blood pressure above 140/90 mm Hg. Hypertension patients at Pinang Jaya Health Center, Bandar Lampung City, are included in the 10 largest diseases which occupy the second highest number suffered by patients. The hypertension treatment cycle is quite long so it must be diagnosed early and treated appropriately. The purpose of this study was to determine the rational use of antihypertensive drugs in hypertensive patients at Pinang Jaya Health Center, Bandar Lampung City based on the right indication, the right diagnosis, the right drug, the right patient, the right dose, the right method of administration and the right time interval for administration. The method used in this study is retrospective which is non-experimental (observational). Data were taken from patient medical records during January-December 2022 and the sample obtained was 104 patients, most of whom were female as many as 85 (81.73%) and patients aged 56-65 years as many as 29 (27.88%). The groups of drugs prescribed were amlodipin 98 (94.23%), captopril 2 (1.92%) and the use of combination therapy drugs, namely amlodipin with captopril 4 (3.85%). The rational use of antihypertensive drugs that meet the rational category of the right diagnosis, the right drug, the right indication, the right patient, the right dose, the right method of administration and the right time interval for administration is 100%. The use of antihypertensive drugs for outpatients at Pinang Jaya Health Center, Bandar Lampung City is rational.